The Use of Nondestructive Evaluation Technology in the Rationalization of costs: An Application In Baghdad Soft Drinks Company " Private Contribution" (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Big developments in technology have led to upset the balance of ideas, given of its own post new properties for products not provided by traditional technology, especially economic units operating within the industrial sector, and therefore it is important to develop the Iraqi industrial sector and interest to do its vital role in light Of progress technological, and the cost accounting has benefited from this technology to development its goals in the regulatory process through the use of non-destructive evaluation perspective in carrying out its functions and to provide appropriate assistance for the use of the products, which were traditional accounting does not take them into consideration. The research aims to a statement that the use technologies (non-destructive) to examine the products rather than analysis or destroyed, thereby generating value. While the important conclusions is that the application of advanced manufacturing technology is not limited to technological change, but there must be a change on the economic unit level representatives of the workers and convince them to accept and support the change, because the benefits can’t be acquired in full only if there is consistency between the unit and technology. And conclude research the need to emphasize the use of non-destructive evaluation methods as the previous control and no subsequent control to that extent or abolished variances by identifying the unit first non-specification of conformance, which then stops the production.